2021
DOI: 10.3390/app11093975
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of ZnBi2O4 Nanoparticles: Photocatalytic Performance for Antibiotic Removal under Different Light Sources

Abstract: This work aims to synthesize a photocatalyst with high photocatalytic performances and explore the possibility of using it for antibiotic removal from wastewater. For that, the spinel ZnBi2O4 (ZBO) was produced with the co-precipitation method and its optical, dielectric, and electrochemical characteristics were studied. The phase has been determined and characterized by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR). For the ZBO morphology, a Scanning Electron Microscopy (SEM) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 65 publications
(90 reference statements)
0
11
1
Order By: Relevance
“…As can be seen, the achieved rate of CFX degradation was 94.34% within 3 h, which demonstrated that CFX was successfully removed using BZO crystals as a photocatalyst. This degradation rate was higher than that obtained using others catalysts during our previous studies [13,14]. As BZO crystals have shown great degradation for CFX, it can be concluded that they can be effective catalysts for the removal of organic pollutants.…”
Section: Degradation Of Organic Pollutantcontrasting
confidence: 56%
See 1 more Smart Citation
“…As can be seen, the achieved rate of CFX degradation was 94.34% within 3 h, which demonstrated that CFX was successfully removed using BZO crystals as a photocatalyst. This degradation rate was higher than that obtained using others catalysts during our previous studies [13,14]. As BZO crystals have shown great degradation for CFX, it can be concluded that they can be effective catalysts for the removal of organic pollutants.…”
Section: Degradation Of Organic Pollutantcontrasting
confidence: 56%
“…Starting with antibiotics, which are a topical example of organic pollutants and are extremely dangerous due to their wide use in both human and veterinary drugs [11], an analysis of antibiotic use has shown that global antibiotic use was recorded at approximately 200,000 tons and has grown by 65% over only 15 years from 2000 and will double by around 2030 [12,13]. This widespread use assures the presence of these antibiotics in different water supplies, in quantities extending from ng/L to µg/L [14]. Taking cefixime (CFX) as an example, it has been detected in various water environments with quantities ranging from 278 to 422 ng/L [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As can be observed, the degradation efficiency of BB41 achieved 98% within just 180 min at pH ~9 and 25 °C. This result can be explained by the gap energy of the catalyst (2.1 eV), which offers a higher absorption in both UV and visible areas from 200 to 800 mm [42]. It was already demonstrated in our previous works [13,14] that the degradation of the dye as an organic compound in the photocatalytic process is mainly due to the reactive oxidative species (ROS) such as superoxide radicals (O2  − ) and hydroxyl radicals ( • OH), where the electrons of Bi12NiO19 conduction band are degraded the Basic Blue 41 by reducing the absorbed O2 to the super-radical anion O2  − .…”
Section: Photocatalytic Activitymentioning
confidence: 98%
“…This process lasts for a few femtoseconds and is then followed by recombination of the excited negative electrons in the conduction band (CB) with the previously generated positive holes at the valence band (VB) either on the surface or in the bulk of the particle releasing heat energy [29][30][31]. Otherwise, these produced charge carriers (e − and h + ) can migrate to the surface of the photocatalyst and initiate further redox or oxidation reactions with adsorbed or reactant molecules on the surface if they have sufficient time or energy, as illustrated in Figure 1, which is inspired from a previous article [16].…”
Section: Fundamental Mechanism For Photocatalytic Processesmentioning
confidence: 99%